An Evaluation of the Modified Diagnostic Criteria for DIC Established by the Japanese Society of Thrombosis and Hemostasis. (September 2017) - Aota, Takumi; Wada, Hideo; Yamashita, Yoshiki; Matsumoto, Takeshi; Ohishi, Kohshi; Suzuki, Kei; Imai, Hiroshi; Usui, Masanobu; Isaji, Shuji; Asakura, Hidesaku; Okamoto, Kohji; Katayama, Naoyuki
Objective: We evaluated the modified diagnostic criteria for disseminated intravascular coagulation (DIC), which was published by the Japanese Society of Thrombosis and Hemostasis (JSTH) in 108 patients with suspected infectious DIC. Material and methods: The diagnoses of the patients were as follows: DIC (n = 63), pre-DIC (n = 22), and non-DIC (n = 45). The efficacy of the diagnostic criteria for DIC was evaluated using a receiver–operating characteristic analysis. Results: Although the area under the curve for global coagulation test (GCT) scores in the diagnosis of "DIC" was high that for the diagnosis of "DIC and pre-DIC" was low, suggesting that the addition of antithrombin (AT), soluble fibrin (SF)/thrombin–AT complex (TAT), and reduced platelet count (PLT) values was required to diagnose "DIC and pre-DIC." Using GCT score with the AT, SF/TAT, and reduced PLT values, the cutoff value of the DIC score for the diagnosis of "DIC and pre-DIC" was 5 points. Discussion and conclusion: The modified JSTH's diagnostic criteria for DIC, which used the GCT score and the reduced PLT, AT, and TAT/SF values, were useful for diagnosing "DIC and pre-DIC."